Caracterização das fibras de colágeno de feridas induzidas em coelhos e tratadas com fibrina rica em plaquetas e rosuvastatina - Breda, Maria Rosa Santos (2019)
In recent years, scientific advances in the healing of skin wounds have been achieved with the use of biomaterials such as autologous platelet-rich fibrin (FRPa) and the use of statins such as rosuvastatin (RSV). The objective of the present study was to evaluate the effect of autologous platelet rich fibrin, rosuvastatin at 1.2%, and associations in the healing of experimentally induced cutaneous lesions on the dorsum of rabbits by means of the quantification of type I and III collagen fibers. Eight clinically healthy, male New Zealand rabbits were used. Four wounds with 8mm punch were made on the back of each rabbit to receive the following treatments: physiological solution (considered wound control), FRPa, RSV and association (FRP + RSV). The treatments were performed on days 3, 7, 10 and 14. On the 17th day, scar biopsies were collected for immunohistochemistry. The treatment with FRPa was the one that produced greater amount of collagen fibers, having the predominance of the collagen type III, because it is an injury still in process of cicatrization. The wound that received only RSV presented a lower amount of COL I, which may be favorable in situations where the animal is most likely to develop hypertrophic scarring. It is concluded that the use of autologous FRP induces a greater amount of type III collagen fibers. The use of RSV may be beneficial in animals that tend to develop a hypertrophic scar.